WALLABY – an SKA Pathfinder H i survey - Koribalski, Bärbel S.; Staveley-Smith, L.; Westmeier, T.; Serra, P.; Spekkens, K.; Wong, O. I.; Lee-Waddell, K.; Lagos, C. D. P.; Obreschkow, D.; Ryan-Weber, E. V.; Zwaan, M.; Kilborn, V.; et al. (Astrophysics and space science, 2020)
The Widefield ASKAP L-band Legacy All-sky Blind surveY ( wallaby ) is a next-generation survey of neutral hydrogen (H i ) in the Local Universe. It uses the widefield, high-resolution capability of the Australian Square Kilometer Array Pathfinder (ASKAP), a radio interferometer consisting of 36 × 12 -m dishes equipped with Phased-Array Feeds (PAFs), located in an extremely radio-quiet zone in Western Australia. wallaby aims to survey three-quarters of the sky ( − 90 ∘ < δ < + 30 ∘ ) to a redshift of z ≲ 0.26 , and generate spectral line image cubes at ∼30 arcsec resolution and ∼1.6 mJy beam −1 per 4 km s −1 channel sensitivity. ASKAP’s instantaneous field of view at 1.4 GHz, delivered by the PAF’s 36 beams, is about 30 sq deg. At an integrated signal-to-noise ratio of five, wallaby is expected to detect around half a million galaxies with a mean redshift of z ∼ 0.05 (∼200 Mpc). The scientific goals of wallaby include: (a) a census of gas-rich galaxies in the vicinity of the Local Group; (b) a study of the H i properties of galaxies, groups and clusters, in particular the influence of the environment on galaxy evolution; and (c) the refinement of cosmological parameters using the spatial and redshift distribution of low-bias gas-rich galaxies. For context we provide an overview of recent and planned large-scale H i surveys. Combined with existing and new multi-wavelength sky surveys, wallaby will enable an exciting new generation of panchromatic studies of the Local Universe. — First results from the wallaby pilot survey are revealed, with initial data products publicly available in the CSIRO ASKAP Science Data Archive (CASDA).